Vagus Nerve Stimulation Amplifies Task-Induced Cerebral Blood Flow Increase - Kunii, Naoto; Koizumi, Tomoyuki; Kawai, Kensuke; Shimada, Seijiro; Saito, Nobuhito (Frontiers in Human Neuroscience, 2021)
Background Vagus nerve stimulation (VNS) is an established palliative surgical treatment for refractory epilepsy. Recently, pairing VNS with rehabilitation received growing attention for their joint effect on neural plasticity. However, objective biological measurements proving the interaction between VNS effects and cortical recruitment are lacking. Studies reported that VNS induced little blood flow increase in the cerebral cortex. Objective This study tested the hypothesis that pairing VNS with a cognitive task amplifies task-induced cerebral blood flow (CBF). Methods This study included 21 patients implanted with vagus nerve stimulator to treat refractory epilepsy. Near-infrared spectroscopy (NIRS) with sensors on the forehead measured CBF changes in the frontal cortices in response to VNS. Cerebral blood flow was measured when VNS was delivered during a resting state or a verbal fluency task. We analyzed the VNS effect on CBF in relation to stimulation intensity and clinical responsiveness. Results We observed no CBF change when VNS was delivered during rest, irrespective of stimulation intensity or responsiveness. Cerebral blood flow changed significantly when a verbal fluency task was paired with VNS in a stimulation intensity-dependent manner. Cerebral blood flow changes in the non-responders showed no intensity-dependency. Conclusion Our results could be an important biological proof of the interaction between VNS effects and cortical recruitment, supporting the validity of pairing VNS with rehabilitation.